Strength training modalities for lower body strength and power: a narrative review - Mohamed Kasim, Mohamad Fajar; Samsudin, Shamsulariffin; Salihan, Safura (Human Resources Management Academic Research Society (HRMARS), 2024)
Strength training is an essential element of athletic conditioning, recovery, and overall well being. The lower body is of greatest significance in strength training, as it plays a key role in a wide range of physical activities, including everyday movements to high performance sports. Lower body strength training is commonly classified into many modalities, such as strength training, plyometric exercises, and functional training. Every modality possesses unique mechanisms and results that can be customised to fulfil specific sports or therapeutic objectives. The literature search technique for this review employed a methodical approach to discover pertinent studies on the influence of various strength training methods on lower body strength and power. The search was performed across many databases, such as PubMed, Scopus, Web of Science, and Google Scholar, to ensure a thorough coverage of the existing literature. The key findings highlight the efficacy of different strength training methods, such as strength training, plyometrics, and mixed training approaches. Future research should investigating the individual differences in response to complex training, such as the impact of age, sex, and genetic factors, can help tailor programs to meet the specific needs of different athletes.